2-step drop impact analysis of a miniature mobile haptic actuator considering high strain rate and damping effects - Choi, Byungjoo; Choi, Hyunjun; Kang, You Sung; Jeon, Yongho; Lee, Moon Gu (Micromachines, 2019)
In recent times, the haptic actuators have been providing users with tactile feedback via vibration for a realistic experience. The vibration spring must be designed thin and small to use a haptic actuator in a smart device. Therefore, considerable interests have been exhibited with respect to the impact characteristics of these springs. However, these springs have been difficult to analyze due to their small size. In this study, drop impact experiments and analyses were performed to examine the damages of the mechanical spring in a miniature haptic actuator. Finally, an analytical model with high strain rate and damping effects was constructed to analyze the impact characteristics.
Keywords: 2-step analysis; Damping effect; Haptic actuators; High strain rates; Impact analysis; Impact characteristics; Mechanical springs; Tactile feedback; 2-step analysis; Damping; Haptic actuator; High strain rate effect; Impact analysis